Characterization and Effectiveness of Moringa Leaves (Moringa oleifera Lamk.) And Azotobacter chroococcum Bio-Organic Fertilizer on the Growth of Green Spinach - Indah Nur Laili; Hendra Susanto (Jurnal Online Pertanian Tropik, 2025)
The decline in spinach production is a challenge in sustainably increasing its productivity. Bio-organic fertilizer made from leaves of Moringa (Moringa oleifera Lamk.) and Azotobacter chroococcum because it contains essential nutrients for plant growth. This study aims to characterize moringa leaf BOF and its effectiveness in increasing green spinach growth. The method used was experimental with 5 treatments namely P1 (10% moringa leaves); P2 (15% moringa leaves); P3 (20% moringa leaves); K- (0% moringa leaves); and K+ (Commercial fertilizer). Parameters observed included pH, temperature, fertilizer color, height, and number of leaves of spinach plants. Fertilizer observation data were analyzed descriptively based on SNI and credible journals, while plant growth data were tested using ANOVA and ANACOVA at the 5% significance level. The BOF produced had a pH of 6-7, a temperature of 26-27 °C, and a dark brown color. The best treatment was P3 which produced an average plant height of 26.6 cm and the highest number of leaves, namely 14 leaves. These results indicate that Moringa leaf BOF has the potential as an effective and environmentally friendly organic fertilizer in increasing the growth of green spinach.